DADS neuropathy associated with anti-TNF-α therapy. (25th November 2015) - McGinty, Ronan Niall; McNamara, Brian; Moore, Helena
Abstract : A 52-year-old man with idiopathic Parkinson's disease and severe rheumatoid arthritis presented with a 1-year history of progressively worsening limb paraesthesia. Examination showed sensory loss in a glove and stocking distribution, absent reflexes and unsteady tandem gait. Nerve conduction studies suggested an acquired peripheral neuropathy with distal demyelination, which—together with the clinical phenotype—was consistent with a Distal Acquired Demyelinating Symmetric (DADS) neuropathy pattern. This was attributed to therapy with adalimumab, an antitumor necrosis factor (TNF)-α agent, which the patient had been taking for 2 years for rheumatoid arthritis. One month after discontinuing adalimumab, the limb paraesthesia had resolved completely and the patient had a normal tandem gait. Demyelinating disorders may rarely occur as complications of anti-TNF-α agents and therefore have implications for pretreatment counselling and ongoing monitoring. DADS neuropathy is a subtype of chronic inflammatory demyelinating polyradiculoneuropathy, which responds poorly to standard therapy and has not previously been described with anti-TNF-α therapy.